Pengaruh Employee Enggament, Training-Development dan Shared Leadership Terhadap Produktifitas Karyawan - Berlianah Berlianah; Yupiter Gulo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to analyze the influence of employee engagement, training and development and shared leadership on work productivity. The object used in this study is PT.Sayap Mas Utama (Wings Corporate) production unit. Sampling using non-probability sampling technique, namely purposive sampling with a total sample used as many as 75 respondents. The technique of collecting data by distributing questionnaires using a Likert scale. The data analysis method used in this study is multiple linear regression. Prior to testing the hypothesis, data were analyzed by testing research instruments, testing classical assumptions and testing models using statistical software program. The result of the study showed that employee engagement, training and development and shared leadership had an effect on work productivity of production unit employees